Abstract and lifelike experimental games - Colman, Andrew Michael (Rhodes University, Faculty of Humanities, Department of Psychology, 1980)
The theory of games seems to me to provide the most promising alternative to the traditional theories of social behaviour. Gaming modelS are inherently social in character (an individual's strategy choice in a game cannot even be properly defined without reference to at least one other individual) and they represent a radical departure from the "social stimulus - individual response" approach. They sean, furthermore, to be the only models which can adequately conceptualize an important (and large) class of social behaviours which arise from deliberate free choice. (From preface)
Keywords: Game theory; Social psychology